2019
DOI: 10.1007/s11307-018-01308-z
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Mutational Status Is Associated with High Glycolytic Activity in ER+/HER2− Early Invasive Breast Cancer: a Molecular Imaging Study Using [18F]FDG PET/CT

Abstract: Purpose: In PIK3CA mutant breast cancer, downstream hyperactivation of the PI3K/AKT/mTOR pathway may be associated with increased glycolysis of cancer cells. The purpose of this study was to investigate the functional association of PIK3CA mutational status and tumor glycolysis in invasive ER+/HER2− early breast cancer. Procedures: This institutional review board-approved retrospective study included a dataset of 67 ER+/HER2− early breast cancer patients. All patients underwent 2-deoxy-2-[ 18 F]fluoro-Dglucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…It has been suggested that other relatively frequent mutations like EGFR and PI3KCA activations correlate with the in situ proliferation and metabolic alterations (e.g., in non-small cell lung cancer — NSCLCs and breast carcinomas). A positive correlation was found among PET-CT SUVmax, EGFR , glycolytic activity, and PI3KCA mutation status in NSCLCs and breast carcinomas [ 31 , 32 ]. These results support the conclusion that not only TP53 and KRAS but also receptor tyrosine kinase pathway mutations are responsible for the metabolic switch to increased glycolysis and reduced OXPHOS [ 32 34 ].…”
Section: Metabolic Consequences Of Frequent Genetic Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that other relatively frequent mutations like EGFR and PI3KCA activations correlate with the in situ proliferation and metabolic alterations (e.g., in non-small cell lung cancer — NSCLCs and breast carcinomas). A positive correlation was found among PET-CT SUVmax, EGFR , glycolytic activity, and PI3KCA mutation status in NSCLCs and breast carcinomas [ 31 , 32 ]. These results support the conclusion that not only TP53 and KRAS but also receptor tyrosine kinase pathway mutations are responsible for the metabolic switch to increased glycolysis and reduced OXPHOS [ 32 34 ].…”
Section: Metabolic Consequences Of Frequent Genetic Mutationsmentioning
confidence: 99%
“…A positive correlation was found among PET-CT SUVmax, EGFR , glycolytic activity, and PI3KCA mutation status in NSCLCs and breast carcinomas [ 31 , 32 ]. These results support the conclusion that not only TP53 and KRAS but also receptor tyrosine kinase pathway mutations are responsible for the metabolic switch to increased glycolysis and reduced OXPHOS [ 32 34 ]. Additionally, epigenetic alterations (e.g., hypermethylation) and PTEN suppression result in PDK1/MYC -dependent Akt/mTOR activation.…”
Section: Metabolic Consequences Of Frequent Genetic Mutationsmentioning
confidence: 99%
“…Another specific tool under investigation has been the use of non-invasive imaging techniques such as PET using radiolabeled antibodies and in particular HER-2 PET/CT to help predict patient benefit from HER-2-directed therapies. 2430…”
Section: Introductionmentioning
confidence: 99%
“…Another specific tool under investigation has been the use of non-invasive imaging techniques such as PET using radiolabeled antibodies and in particular HER-2 PET/CT to help predict patient benefit from HER-2-directed therapies. [24][25][26][27][28][29][30] Angiogenesis plays a driving role in cancer development and progression 31,32 and has been defined as one of the hallmarks of cancer. 33 Data from breast cancer show that angiogenesis in the primary cancer can predict for disease-free and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Нарушения онкогенного сигнального каскада PI3K/Akt/mTOR встречаются практически при всех злокачественных новообразованиях человека, а соматические мутации PIK3CA выявляются примерно в 1/3 опухолей молочной железы [7][8][9]. Повреждения PIK3CA приводят к разнообразным функциональным последствиям, например, влияют на пролиферацию и выживаемость клеток, метаболические особенности, иммуногенность, предпочтительные зоны метастазирования и даже специфические паттерны роста опухоли, которые можно определить радиологически [10][11][12][13][14]. Мутации PIK3CA являются наиболее частым генетическим дефектом при ER+/HER2-РМЖ (28-47%); при этом они реже встречаются при HER2-позитивных (22-40%) и трижды негативных опухолях (8-18%) [5,7,[15][16][17].…”
unclassified